Problem Formulation in Planning and Design - Volkema, Roger J. (Management Science, 1983)
This paper deals with the role of problem formulation in planning and design, including: (a) the importance of problem formulation to planning and design; (b) problematic, physiological, psychological and environmental factors that can affect the formulation process; and (c) problem formulation heuristics. Two types of formulation heuristics are identified—problem reduction and problem expansion. Because the latter type has received little empirical research, an initial study of a problem expansion heuristic (Problem-Purpose Expansion) was conducted. Experimentation showed that Problem-Purpose Expansion may have a positive effect on idea generation, particularly for individuals working on problems that fall outside their area of expertise. Exhorting the importance of problem formulation, a second treatment studied in these experiments, produced little measurable effect on idea generation.